THE EFFECT OF MURABAHAH FINANCING, FINANCING DEPOSIT RATIO (FDR), AND THIRD PARTY FUNDS ON PROFITABILITY WITH NON-PERFORMING FINANCING (NPF) AS A MODERATING VARIABLE IN BPRS. - Indah Dwi Navita; Achmad Fauzi; Indah Muliasari (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2023)
In the realm of Islamic banking and finance, the mechanisms and factors influencing the profitability of Islamic financial institutions have garnered significant attention from researchers and practitioners alike. Islamic People's Financing Banks, as specialized entities operating under Islamic financial principles, play a vital role in offering financial services that adhere to Shariah principles. This study aims to investigate the impact of Murabahah Financing, Financing Deposit Ratio (FDR), Third-Party Funds (DPK), and Non-Performing Financing (NPF) on Profitability in Islamic People's Financing Banks in Indonesia. The research employs a quantitative approach, utilizing documentation techniques and secondary data collected from BPRS financial reports available on the Financial Services Authority (OJK) website for the 2020-2021 period. The sample selection employs a random sampling technique, resulting in a total of 132 samples. The study employs various data analysis methods, including descriptive statistical analysis, tests for classical assumptions, multiple linear regression, and moderated regression analysis. Based on the partial results of the study, it is observed that Murabahah Financing, Financing Deposit Ratio (FDR), and Third-Party Funds (DPK) do not exhibit a significant influence on profitability. Conversely, Non-Performing Financing (NPF) demonstrates a significant negative impact on profitability. Furthermore, with the inclusion of NPF as a moderating variable, the research findings indicate that NPF is unable to moderate the effects of Murabahah Financing, FDR, and Third-Party Funds on Return on Assets (ROA).